Ta'mim Qoym al-Ittisal al-Lughawi Fi al-Insijam al-Dini - Yufi Mohammad Nasrullah (ALSINATUNA, 2017)
The majority of the population in Bandung is almost Muslim. On the other hand, the people of this region are of different ethnicities and religions that deal with each other in their daily lives. However, this situation of the religious life between Muslims and nonMuslims in Bandung is harmonious. If it is not properly managed, new problems with social stability may arise, and therefore living together in religious life in Bandung City should be maintained to promote social solidarity. Thus, this research came as a serious way to find points that are likely to be involved in the process of communication between different religions, to be carried out by scientists, experts and socialists while applying. This means that if the conditions prevailing in life are consistent or found problems among the Muslims themselves, and other religious people. the solution of these problems is concentrated in one of the potential sites, and this study works to create social communication through linguistic communication using the language of religiosity (religious terms). The data collection was taken through personal interview, observation and study of documents, and the number of persons examined in the interview reached thirteen people from all the religious leaders who are considered by their community scientists.